Development and evaluation of a COVID tracking system to support provision of social service in Wyandotte County, Kansas - Wexler, Catherine; Dixon, Katelyn Sanner; Oyowe, Kevin; Lapke, Brooke; Conner, Hannah; Shoemaker, Hailey; Corriveau, Erin; Greiner, Allen; Finocchario-Kessler, Sarah (Frontiers in Public Health, 2023)
Background In addition to the state-mandated case investigation and contact tracing, the Unified Government Public Health Department of Wyandotte County, Kansas implemented social support services for COVID-19 cases and contacts; however, did not have the systems in place to document the provision of these services. Our team worked with the health department to develop and implement the COVID Tracking System (CTS), an eHealth system that linked multiple involved teams. Here, we describe the development and evaluation of the CTS. The objective of this manuscript is to describe and evaluate the development and implementation process of the Covid Tracking System. Methods Drawing from concepts of user-centered design, we took a 4-phase approach to development: understanding context, specifying needs, designing solutions, and evaluating. A mixed-methods evaluation of the development and implementation process using RE-AIM was conducted. Quantitative CTS data captured between February 1, 2021, and September 30, 2021 were exported. Descriptive statistics were calculated for categorical variables and means (SD, range) or median (IQR) for continuous variables. Qualitative discussions with key users supplemented the quantitative data. Results There were 1,152 cases entered into the CTS, of whom 307 (26.6%) requested a letter be sent to their workplace to excuse them during their quarantine period, 817 (70.9%) requested and had food and cleaning supplies delivered, 21 (1.8%) requested guidance on applying for federal assistance, and 496 (43.1%) requested to be contacted by a community health worker. While a few technical glitches slowed down early implementation, these were quickly resolved and key users felt that the CTS streamlined client referral and simplified their workflow, allowing them to spend more time on patient care and follow up, rather than documentation. After study implementation ended, the Unified Government Public Health Department of Wyandotte County continued using the CTS for client tracing and follow up. Discussion This project provides a roadmap of how user centered design can be applied to the development and evaluation of eHealth software to support program intervention implementation, even in situations where urgent action is needed.